THEORETICAL ANALYSIS OF DRIVING FORCES OF COTTON PIECES ENTERING THE SEPARATOR WORKING CHAMBER (American Journal of Interdisciplinary Research and Development, 2024)
In this article, a theoretical study of the condition of entering the cotton ball into the separator through the air transport device and hitting the working chamber That is why impact of cotton particles entering the separator working chamber together with the air flow on the elastic plank located at a certain distance from the entrance path and forming an angle with the vertical direction, and the impact process between the cotton particles and the elastic plank is theoretically analyzed. When the cotton raw material sticks to the mesh surface, as a result of air absorption from the mesh surface, the process of cleaning from the small impurities in the cotton raw material in a passive state occurs.The air flow is sucked in through the slits of the mesh surface located after the elastic plank in its direction. The mesh surface is in the form of a conveyor belt, which moves regularly. Graphs of changes in the movement of a piece of cotton from the surface of the entrance to the separator to the elastic plate. Methods of conducting research and tests. A theoretical study of the movement of cotton pieces to an elastic plank. Mathematical model developed graphs are built.